DESIGNING AND MANAGING SMART SERVICES IN THE SOCIAL AND HEALTH SECTOR - Valkama, Katja; Salminen, Merja (Revista Prâksis, 2019)
ABSTRACT In this article, smart services are considered in the social and health care context. It is argued that new tools and information will help professionals, managers, and decision makers solve problems. Artificial intelligence, personalized medicine, social innovations, and the responsible use of social and health care data will create new services and improve access to all services. Organizational intelligence, smart services, and smart care are just some examples of the rhetoric that strengthens today’s discussions on social and health care in Finland. In conclusion, it is argued that developing and using smart services in social and health care have to be based on the user’s active role in smart service design processes. Management structures should support and encourage practices where the user’s involvement and participation is self-evident. Keywords: Smart social and health care. Services. Wellbeing. RESUMO Neste artigo, os serviços inteligentes são analisados no contexto social e de saúde. Argumenta-se que as novas ferramentas e informações ajudarão os profissionais, os gerentes e os tomadores de decisão a resolverem problemas. A inteligência artificial, a medicina personalizada, as inovações sociais, bem como o uso responsável de dados sociais e de saúde criarão novos serviços e melhorarão o acesso a todos os serviços. A inteligência organizacional, os serviços inteligentes e o atendimento inteligente são apenas alguns exemplos da retórica que fortalece as discussões atuais sobre a assistência social e de saúde na Finlândia. Em conclusão, argumenta-se que o desenvolvimento e o uso de serviços inteligentes em serviços sociais e de saúde devem se basear no papel ativo do usuário nos processos de desenho de serviços inteligentes. As estruturas de gestão devem apoiar e encorajar práticas onde o envolvimento e a participação do usuário sejam evidentes. Palavras-chave: Assistência social e saúde inteligente. Serviços. Bem-estar.